2001
DOI: 10.1002/cplx.10021
|View full text |Cite
|
Sign up to set email alerts
|

How neutral networks influence evolvability

Abstract: Evolutionary algorithms apply the process of variation, reproduction, and selection to look for an individual

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 38 publications
2
86
0
Order By: Relevance
“…Conflicting opinions have been proposed with regard to the effects of neutrality on evolutionary search. While some studies have found no benefit [2,3,4], others have claimed that neutrality provides a buffer against deleterious genetic perturbation [5,6] and reduces the risk of premature convergence through an expansion of the search space [7,8]. As argued in [9], the lack of consensus regarding the benefits of neutrality largely stem from the overly complex problems, representations, and search algorithms used in these analyses, which make it difficult to tease apart the effects of neutrality from other confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting opinions have been proposed with regard to the effects of neutrality on evolutionary search. While some studies have found no benefit [2,3,4], others have claimed that neutrality provides a buffer against deleterious genetic perturbation [5,6] and reduces the risk of premature convergence through an expansion of the search space [7,8]. As argued in [9], the lack of consensus regarding the benefits of neutrality largely stem from the overly complex problems, representations, and search algorithms used in these analyses, which make it difficult to tease apart the effects of neutrality from other confounding factors.…”
Section: Introductionmentioning
confidence: 99%
“…Ebner et al [24], [25] argued that these types of mappings are particularly interesting since they seem to allow neutral networks that are intertwined with a high degree of connectivity. This property allows the finding of more species compared with other types of mappings.…”
Section: Previous Work On Neutralitymentioning
confidence: 99%
“…In [19,20], Ebner et al extended the previous investigation of [75,77]. For this purpose, the authors analysed the effects of the RBN mapping and the cellular automaton (both described previously) in the context of what they called phenotype-species mapping.…”
Section: Genotype-phenotype Mappings -Definitions and Propertiesmentioning
confidence: 99%